THE CLOSED TECHNIQUE IN THE TREATMEMT OF PILONIDAL SINUS GIVES SUPERIOR RESULTS TO THE CONVENTIONAL OPEN TECHNIQUE; A PROSPECTIVE STUDY - Safwan A Taha (Basrah Journal of Surgery, 2005)
The aim of this study is to compare between excision followed by primary closure as the first type of treatment and excision with laying the tract open, to heal by granulation, as a second type of treatment of pilonidal sinus. Seventy three patients were included in the study. They were divided randomly into two groups, group A and group B, the first group was treated by closed method and the other by open method. Data were collected and analyzed regarding recurrence rate, time needed for full healing, infection rate and duration of hospital stay. Thirty-five patients comprised group A (30 males and 5 females) compared to 38 patients in group B (31 males and 7 females). The mean hospital stay for group A ranged from 3 to 6 days (mean=4.4 days) while for group B it ranged from 1 to 2 days (mean=1.2 days), a difference that is statistically extremely significant (P value <0.00001). The rate of wound infection was similar (2.8%) in both groups (one in 35 patients of group A and one in 38 patients of group B). Primary closure has the advantages of quicker healing time, shorter post operative specialized medical care and less time off work.